Reaksi Pasar Modal Indonesia Terhadap Kebijakan Tax Amnesty Indonesia pada Saham LQ45 Tahun 2016-2017 - Ramaditya Dwi Nanda; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2017)
Events or domestic foreign policies can influence investors' decisions in the capital market. The existence of these events certainly contain an information that can be interpreted by investors to conduct transactions on the capital market. The tax amnesty policy of Indonesia is assumed to have information content capable of responding to capital market actors. The reaction of capital market actors can be measured by the abnormal return and increased trading volume of activity. So it is necessary to do research on the reaction of the capital market to the tax amnesty policy of Indonesia on LQ45 stock index. The population in this study were 45 companies included in LQ45 during the study period taken by purposive sampling technique. This study uses the method of event study analysis with 11-day period of research on t-5 to t + 5 t0 as event date in all tax amnesty policy periods during that period, period I (July 1, 2016-30 September 2016), period II (October 1, 2016 -31 December 2016) and the third period (January 1, 2017- March 31, 2017). Technique of research analysis using test wilcoxon signed rank test. The result of the research is that there is no difference of average abnormal return and trading volume activity obtained by investor at the time before and after the announcement period I tax amnesty. Period II indicates that there is no difference in average abnormal return but trading volume activity shows negative and significant difference before and after the announcement of II tax amnesty period. In the third period of tax amnesty policy shows that there is a difference in average abnormal return is positive but trading volume activity does not show significant difference at the time before and after the announcement period III tax amnesty. The results explained that the tax amnesty information was not responded by investors in the first period of tax amnesty policy. Period II tax amnesty policy indicates a negative difference due to the hardbrexit issue affecting Asian exchanges including Indonesia. Investors tend to be waiting for the success of tax amnesty which in the third period there is a reaction indicating a positive abnormal return. Based on the repatriated funds collected, investors are more interested in investing in the banking sector than the LQ45 index sector. As a suggestion, there will be better if investors analyze issues such as tax amnesty issues that are assumed to be a positive issue. Because not all information circulating in line with the reality that exist in the market, this is done so that investors get the maximum return or free from risk.